Effect of Corn Type and Form of Supplement on Grazing Steers – Year 3 - Jaymelynn K. Farney; Kloey Rash; Noelle Collins; Emily Black; Hailey Gillespie (Kansas Agricultural Experiment Station Research Reports, 2024)
Eighty stocker steers were grazed on bromegrass from the middle of May to the beginning of November and were provided five different feeds while on grass during the summer. Treatments evaluated included (1) mineral only; (2) free-choice supplementation in the form of liquid feed (MIX30), or (3) block format (Mintrate 40 Red); and hand-fed supplements of 60% corn:40% dried distillers grains at 0.5% of body weight on a dry matter basis offered daily where the corn was either an (4) isoline corn (ISO; parent genetic line) or (5) Enogen feed corn (ENO; includes the alpha-amylase gene). Steers were weighed every 28 days while on grass and were measured for carcass quality by ultrasound prior to being placed in feedlot. Hand-fed steers had greater gain than self-fed supplemented steers and these hand-fed steers tended to have more muscle depth coming off grass than other supplemented steers. There was no difference in backfat nor marbling scores off grass for any treatments evaluated. Loin muscle depth was greater for supplemented steers as compared to non-supplemented. Overall, if a steer was supplementally fed, it had 64 pounds more weight than if fed a mineral only, and this advantage was driven primarily by hand-fed supplements. However, each operation needs to calculate cost of production and ease of feeding daily over the convenience of self-fed supplements.
Keywords: amylase corn; protein block; liquid feed; hand-fed